CORRECTION OF VITAMINS AND MICROELEMENTS DEFICIENCY IN CHILDREN UNDER PRESCHOOL AND SCHOOL AGE - I.N. Zakharova (Voprosy Sovremennoj Pediatrii, 2009)
The article presents basic data on nutrition and vitamins and microelements deficiency in children under preschool and school age in Russia. The etiology of vitamins insufficiency is described. Authors observe the opportunities of vitamins and microelements deficiency correction with special children’s vitamin and mineral complexes.Key words: children, adolescents, vitamins, microelements, deficiency, vitamin-mineral complexes, adverse reaction.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(5):106-110)